Brief Motivational Interventions for College Student Problem Gamblers - Petry, Nancy M. (2009)
AIMS: College students experience high rates of problem and pathological gambling, yet little research has investigated methods for reducing gambling in this population. This study sought to examine the efficacy of brief intervention strategies. DESIGN: Randomized trial. SETTING: College campuses. PARTICIPANTS: 117 college student problem and pathological gamblers. INTERVENTIONS: Students were randomly assigned to: an assessment-only control, 10 minutes of Brief Advice, 1 session of motivational enhancement therapy (MET), or 1 session of MET plus 3 sessions of cognitive-behavioral therapy (CBT). The three interventions were designed to reduce gambling. MEASUREMENTS: Gambling was assessed at baseline, week 6, and month 9 using the Addiction Severity Index-Gambling (ASI-G) module, which also assesses days and dollars wagered. FINDINGS: Compared to the assessment-only condition, those receiving any intervention had significant decreases in ASI-G scores and days and dollars wagered over time. The MET condition significantly decreased ASI-G scores and dollars wagered over time, and it increased the odds of a clinically significant reduction in gambling at the 9-month follow-up relative to the assessment-only condition, even after controlling for baseline indices that could impact outcomes. The Brief Advice and MET+CBT conditions had benefits on some, but not all, indices of gambling. None of the interventions differed significantly from one another. CONCLUSIONS: These results suggest the efficacy of brief interventions for reducing gambling problems in college students.